Methylation of SPRED1: A New Target in Acute Myeloid Leukemia - Su, Nan; Wang, Yujiao; Lu, Xianglan; Xu, Weihong; Wang, He; Mo, Wenbin; Pang, Hui; Tang, Rurong; Li, Shibo; Yan, Xiaojing; Li, Yan; Zhang, Rui (Frontiers in Oncology, 2022)
Sprouty-related, EVH1 domain-containing protein 1 (SPRED1) has been identified as a novel tumor suppressor gene in AML. Previous studies showed that SPRED1 methylation levels were significantly increased in AML patients, making it an interesting candidate for further investigations. To confirm the association of SPRED1 methylation, clinical parameters and known molecular prognosticators and identify the impact of methylation level on treatment outcome, we conducted this study in a larger cohort of 75 AML patients. Significantly increased methylation level of SPRED1were detected at four of ten CpG units by quantitative high-resolution mass spectrometry-based approach (MassARRAY) in AML patients. Whereas overall survival (OS) and relapse-free survival (RFS) showed no statistical difference between hypermethylation and hypomethylation subgroups, the relationship between methylation level and treatment response was indicated in paired samples from pre- and post-induction. To determine the possible mechanism of SPRED1 methylation in AML, we performed in vitro experiments using THP-1 cells, as the latter showed the highest methylation level (determined by utilizing Bisulfite modification) among the three AML cell-lines we tested. When treated with 5-AZA and lentivirus transfection, up-regulated SPRED1 expression, decreased cell proliferation, increased cell differentiation and apoptosis and inactivated phosphorylated extracellular signal-regulated kinase (p-ERK) were detected in THP-1 cells. These results show that demethylation of SPRED1 can inhibit the proliferation of AML cells and promote their differentiation and apoptosis, possibly by ERK pathway. The hypermethylation of SPRED1 is a potential therapy target for AML.